A robust biocatalyst based on laccase immobilized superparamagnetic Fe3O4@SiO2–NH2 nanoparticles and its application for degradation of chlorophenols. (March 2022) - Chen, Zhihui; Yao, Jun; Ma, Bo; Liu, Bang; Kim, Jonghyok; Li, Hao; Zhu, Xiaozhe; Zhao, Chenchen; Amde, Meseret
Abstract: The presence of chlorophenols in water and wastewater is considered a serious environmental issue. To eliminate these micropollutants, biodegradation of chlorophenols using enzyme-nanoparticle conjugated biocatalyst, is proposed as an economical and eco-friendly method. Herein, amino-functionalized superparamagnetic Fe3 O4 @SiO2 –NH2 nanoparticles with core-shell structure were constructed as a promising carrier for immobilization of laccase from Trametes versicolor . Compared with free laccase, Fe3 O4 @SiO2 –NH2 -Laccase displayed remarkable outcomes in all major areas such as temperature and storage stabilities, and tolerance to organic solvents and metal ions. The biocatalytic performance and reusability of Fe3 O4 @SiO2 –NH2 -Laccase were evaluated for the degradation of 2, 4-dichlorophenol (2, 4-DCP) and 2, 4, 6-trichlorophenol (2, 4, 6-TCP) in repeated cycles. Even after 10 successive reuses, the degradation rate of 2, 4-DCP and 2, 4, 6-TCP were found to be 54.9% and 68.7%, respectively. The influences of solution pH, initial chlorophenol concentration, and temperature on the degradation rate of these two chlorophenols were evaluated. The degradation intermediate products including dimers, trimers, and tetramers of 2, 4-DCP and 2, 4, 6-TCP were identified. Release of chloride ions was observed during the enzymatic degradation of these two chlorophenols. Based on the determination of intermediate products and released chloride ions, the degradation pathway that was involved in dehydrogenation, reactive radical intermediates formation, dechlorination, self-coupling and oligomers/polymers formation was proposed. The toxicity of these two chlorophenols and their intermediates was substantially reduced during the enzymatic degradation. The results of this study might present an alternative clean biotechnology for the remediation of 2, 4-DCP and 2, 4, 6-TCP contaminated water matrices. Graphical abstract: Image 1 Highlights: The biocatalyst exhibited efficient recyclability and reusability. Degradation predominantly generated various structural oligomers/polymers. Degradation of 2, 4-DCP and 2, 4, 6-TCP is accompanied by dechlorination. The degradation mechanism of 2, 4-DCP and 2, 4, 6-TCP was elucidated. Toxicity was substantially reduced with the degradation of 2, 4-DCP and 2, 4, 6-TCP.